Spiritual Intelligence as a Key to Auditor Performance: Kecerdasan Spiritual sebagai Kunci Kinerja Auditor - Andari, Miranda Putrin; Hermawan, Sigit (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Auditor performance plays a crucial role in ensuring the credibility of financial statements and decision-making in the business sector. Specific Background: Factors such as audit experience, role ambiguity, and a healthy lifestyle are believed to shape auditor performance, yet the mediating influence of spiritual intelligence remains underexplored. Knowledge Gap: Previous studies have rarely integrated spiritual intelligence as an intervening variable connecting professional experience, psychological aspects, and lifestyle with auditor performance. Aims: This study investigates how audit experience, role ambiguity, and healthy lifestyle relate to auditor performance through spiritual intelligence as a mediating variable among auditors in Surabaya. Results: Using Partial Least Squares (PLS) with 65 respondents, the findings reveal that role ambiguity and spiritual intelligence significantly affect auditor performance, while audit experience and healthy lifestyle do not. Spiritual intelligence effectively mediates the relationship between audit experience and performance but not for role ambiguity or healthy lifestyle. Novelty: This research integrates behavioral, spiritual, and professional dimensions in explaining auditor performance. Implications: Enhancing auditors’ spiritual intelligence can strengthen ethical awareness, decision quality, and professional resilience in complex audit environments.Hightlight: Spiritual intelligence mediates auditor performance dynamics. Behavioral and professional factors are integrated. Supports sustainable ethical auditing practices. Keywords: Auditor Performance, Spiritual Intelligence, Audit Experience, Role Ambiguity, Healthy Lifestyle